Missing Growth in Finland - Juho Anttila (The Research Institute of the Finnish Economy (ETLA), 2018)
This study investigates the extent of 'missing growth' in Finland due to upward bias in the cost-of-living measurement. This upward bias, as documented by Aghion et al. (2017), results from the quality adjustments that statistical offices use for entering and exiting products. This bias is estimated using a method by Aghion et al. (2017), which is based on establishments' entry- and exit-dynamics. The baseline result suggests an average missing growth of 0.69 percentage points over the years 2006–2013. Additionally, product- and establishment-level data are used to study the identification assumptions behind the market share method. This study's results raise some concerns regarding the validity of these assumptions.
Keywords: O3; O4; 330; Inflation measurement; Creative destruction; Economic growth